2005
DOI: 10.1016/j.neuron.2005.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Triheteromeric NMDA Receptors by N-Terminal Domain Ligands

Abstract: NMDA receptors (NMDARs) are heteromeric assemblies of NR1 and NR2(A-D) subunits with properties heavily influenced by the type of NR2 subunit incorporated. While NMDARs with only one type of NR2 subunit have been extensively characterized, little is known about receptors containing two different NR2 subunits, despite compelling evidence that such triheteromeric receptors exist in vivo. We used a point-mutation approach that allows isolation of recombinant triheteromeric NMDARs possessing two different NR2 N-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
233
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(252 citation statements)
references
References 50 publications
16
233
3
Order By: Relevance
“…If the NMDA-EPSC were mediated by receptors composed of two distinct diheteromeric populations, then removal of the slower NR1/NR2B NMDAR current, using either Ro 25-6981 or ifenprodil, would result in an alteration of kinetics, as seen in the hippocampus from 2-week-old rat hippocampus (Bartlett et al, 2006). In support of this, recent experiments demonstrated that ifenprodil has a much reduced efficacy, but similar potency, of inhibition of triheteromeric vs diheteromeric NMDARs, consistent with our observed incomplete inhibition of the NMDA-EPSC by Ro 25-6981 and ifenprodil (Hatton and Paoletti, 2005). When extrapolated to a synaptic response, if the receptors were primarily triheteromeric, the application of an NR2B-selective antagonist would inhibit all receptors and thus would not selectively remove any one component, resulting in no change in kinetics (illustrated in Figure 6B).…”
Section: Nmdar Composition In the Vbnstsupporting
confidence: 89%
See 1 more Smart Citation
“…If the NMDA-EPSC were mediated by receptors composed of two distinct diheteromeric populations, then removal of the slower NR1/NR2B NMDAR current, using either Ro 25-6981 or ifenprodil, would result in an alteration of kinetics, as seen in the hippocampus from 2-week-old rat hippocampus (Bartlett et al, 2006). In support of this, recent experiments demonstrated that ifenprodil has a much reduced efficacy, but similar potency, of inhibition of triheteromeric vs diheteromeric NMDARs, consistent with our observed incomplete inhibition of the NMDA-EPSC by Ro 25-6981 and ifenprodil (Hatton and Paoletti, 2005). When extrapolated to a synaptic response, if the receptors were primarily triheteromeric, the application of an NR2B-selective antagonist would inhibit all receptors and thus would not selectively remove any one component, resulting in no change in kinetics (illustrated in Figure 6B).…”
Section: Nmdar Composition In the Vbnstsupporting
confidence: 89%
“…(Bb) A schematic representation of the effects of an NR2B antagonist on triheteromeric receptors. Recent evidence (Hatton and Paoletti, 2005) demonstrated that NR2B antagonists can inhibit triheteromeric receptors, albeit with reduced efficacy, as demonstrated with the reduced amplitude of the traces as compared to those in b1. However, it is important to note the lack of alteration in the decay kinetics, reflecting the results obtained in the vBNST.…”
Section: Nmdar Composition In the Vbnstmentioning
confidence: 99%
“…Because of the lack of a selective antagonist for these receptors, their contributions to cell survival and/or death remain to be determined. Given that Ro 25-6981 has a much higher potency toward the NR1/NR2B diheteromeric receptors than NR1/NR2A/NR2B triheteromeric receptors (Hatton and Paoletti, 2005), it is reasonable to speculate that most of the NMDA-induced cell death actions observed in the present study are primarily a result of activation of NR1/NR2B receptors. In contrast, although the sensitivity of NVP-AAM077 toward the NR1/NR2A/NR2B triheteromeric receptors has not been investigated previously, because NVP-AAM077 is a competitive antagonist at the agonist binding sites of NR2A subunits and because both binding sites need to be occupied to open the channel, we speculate that NVP-AAM077 may inhibit all NR2A-containing receptors.…”
Section: Discussionmentioning
confidence: 70%
“…However, several recent studies have demonstrated that such a marginal effect may not significantly alter the utility of NVP-AAM077 as an NR2A-subunit preferential antagonist under experimental conditions such as in the present study Massey et al, 2004;Tigaret et al, 2006). Previous studies have indicated that Ro 25-6981 specifically blocks NR1/NR2B diheteromeric NMDA receptors with little effect on NR1/ NR2A/NR2B triheteromeric NMDA receptors (Hatton and Paoletti, 2005). The relative potency of NVP-AAM077 for NR1/ NR2A/NR2B versus NR1/NR2A receptors remains to be determined; however, considering that NVP-AAM077 is a competitive antagonist at glutamate binding sites, and that both glutamate binding sites must be occupied to open the channel Westbrook, 1991, 1994), it is likely able to block all NR2A-containing NMDA receptors.…”
Section: Resultsmentioning
confidence: 98%
“…NMDARs containing the NR2A subunit exhibit high affinity voltage-independent inhibition by Zn 2+ [23]. The molecular determinants of high affinity zinc binding have been demonstrated to lie in the amino terminal domain of the NR2A subunit [24]. Studies of Gielen et al [25] and Erreger et al [26] suggest an allosteric interaction between Zn 2+ and glutamate binding domains on NR2A.…”
Section: Discussionmentioning
confidence: 99%